Nutrient Inadequacy Is Prevalent in Pregnant Adolescents, and Prenatal Supplement Use May Not Fully Compensate for Dietary Deficiencies. (June 2014) - Lee, Sunmin; Young, Bridget E.; Cooper, Elizabeth M.; Pressman, Eva; Queenan, Ruth Anne; Olson, Christine M.; Guillet, Ronnie; O'Brien, Kimberly O.
A longitudinal study was undertaken in 156 pregnant adolescents (≤18 years old) to characterize dietary intake and to determine the degree to which prenatal supplement use compensates for dietary deficits. The adequacy of dietary intake was assessed by comparing self-reported intake from up to three 24-hour dietary recalls with the dietary reference intakes. The majority of teens did not meet the estimated average requirements (EAR) for vitamin D (93%), vitamin E (94%), Mg (90%), Fe (76%), and Ca (74%). More than half of the adolescents in each gestational window (<23 weeks; 23-30 weeks; and ≥31 weeks of gestation) self-reported daily use of prenatal supplements, but the additional supplement contributions were not sufficient to meet the EAR for Mg (90%) or Ca (54%). Pregnant adolescents are at risk for insufficient intake of several essential nutrients from diet alone in spite of adequate or excessive energy intakes. Daily use of prenatal supplements reduces the prevalence of dietary inadequacy for many nutrients but may not be sufficient to meet the requirements for Mg and Ca. Practitioners should identify motivators and barriers to adequate diet and prenatal supplement use in order to address key nutrients of concern.